2006
DOI: 10.1051/forest:2006012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of drought and leaf development stage on enzymatic antioxidant system of twoPopulus deltoides×nigraclones

Abstract: -Impacts of mild and severe water constraints were investigated on leaf protein content and activities of superoxide dismutase (SOD), catalase and peroxidase in young cuttings of two Populus deltoides × nigra clones, 'Luisa_Avanzo' and 'Dorskamp', known to differ in their level of drought tolerance. Expanding and mature leaves were analyzed separately. The effect of water deficit on enzymatic antioxidant system depended on both clone and leaf development stage. For 'Dorskamp', which presents an higher drought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The rise in the activity of APX was observed in parallel to the decline of lipid peroxidation and the increase of Φ PSII . The separated SOD isoforms can be identified as I: MnSOD, II: Cu/ZnSOD, III: FeSOD and IV: Cu/ZnSOD [48][49][50]. As, in contrast to the MnSOD that is present in peroxisomes, mitochondria and cell wall [51], the activities of chloroplast Cu/ZnSOD isoforms (II and IV) did not increase during the experiment, their role in Cd stress alleviation may be less important in poplar.…”
Section: Antioxidative Defencementioning
confidence: 99%
“…The rise in the activity of APX was observed in parallel to the decline of lipid peroxidation and the increase of Φ PSII . The separated SOD isoforms can be identified as I: MnSOD, II: Cu/ZnSOD, III: FeSOD and IV: Cu/ZnSOD [48][49][50]. As, in contrast to the MnSOD that is present in peroxisomes, mitochondria and cell wall [51], the activities of chloroplast Cu/ZnSOD isoforms (II and IV) did not increase during the experiment, their role in Cd stress alleviation may be less important in poplar.…”
Section: Antioxidative Defencementioning
confidence: 99%
“…Especially a decreased photosynthetic rate is a common phenomenon in poplars under drought stress (Yin et al, 2005;Xu et al, 2008aXu et al, , 2009. Drought also causes an accumulation of reactive oxygen species (ROS) and, subsequently, induces oxidative stress on plant cells (Lei et al, 2006;Marron et al, 2006;Xiao et al, 2009). To reduce the negative consequences, trees have evolved various protective mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme is involved in antioxidant protection and maintenance of membrane integrity (Carvalho et al, 2012). Marron et al (2006) showed an increase in CAT activity in leaves of Populus deltoides clones. Slight peaks in the APX enzyme were observed with a subsequent decrease in its activity in both tissues.…”
Section: Discussionmentioning
confidence: 99%